Development of Mobile Learning Based E-Module to Improve Concept Understanding and Interest Learning X Class Student in Momentum and Impulse - Angela Gusti Ayu Gita Sukmadewi; J Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop multiple representation-based electronic modules with the help of mobile physics learning on momentum and impulse material in class X MIPA. The research wants to test the effectiveness of e-modules based on their validity in increasing students' understanding of concepts and learning interest. The research method used is quantitative with the 4D model (Define, Design, Develop, and Disseminate). The subjects of this research were students in class X MIPA 2 and X MIPA 4 SMA Negeri 1 Kalasan. The research design used was one group pretest-posttest research design. There are two instruments used, namely test and non-test instruments, as well as data analysis techniques using Microsoft Excel. The results of the study show that the use of multiple representation e-modules assisted by physics learning cars is feasible to be used as teaching materials. In addition, the results of differences in pretest and posttest scores and interest in learning in the modeling class were 86% and in the implementation class were 88% indicating an increase in learning interest received by students.